Schiffswracks im schleswig-holsteinischen Wattenmeer: Zum Stand der aktuellen Forschung - Zwick, Daniel (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
Between 2016 and 2020, four new shipwrecks were discovered in Schleswig- Holstein‘s Wadden Sea as a result of coastal erosion. In 2022, two additional shipwrecks were exposed by hurricanes. All wrecksites are located in the intertidal zone, i. e. on Hörnum Odde (island of Sylt), as well as the outer shoals of Japsand and Süderoogsand, which form part of the North Frisian barrier islands and have been navigation hazards since time immemorial. The investigated wrecks date between the 17th and 20th centuries AD. Some remarkable constructional features could be observed, which allow inferences on the wrecks‘ origins and shipbuilding traditions. Two of the wrecks feature double- planking carried out in the characteristic Dutch-style shell-first technique that was – until recently – regarded as a fleeting phenomenon of the late 16th and early 17th centuries, but based on these new discoveries, this peculiar construction can now be traced to the mid-18th century. In general, the North Frisian Wadden Sea was a heavily Dutch-influenced area, which finds not only expression in the majority of shipwrecks, but also the maritime culture of the islands. Another aspect worth noting in the context of archaeological research in the intertidal zone is the involvement of local citizens, who facilitate the work of the archaeologists in these remote areas with vital logistical support and knowledge of the local environment. This highlights the public responsibility of 208 archaeologists to involve and share their knowledge with the local community. This paper will provide an overview of the investigated shipwrecks and an update on interim research results.